Kuantitas Produksi Telur Puyuh (Coturnix coturnix japonica L) Setelah Pemberian Cahaya Monokromatik - Utami, Yuli Tri; Mardiati, Siti Muflichatun; Kasiyati, Kasiyati; Saraswati, Tyas Rini (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2016)
Light is one of the most important environmental aspects in poultry production. The intensity, duration, and light color are used to improve the behavior, activity, production performance, and reproduction of poultry. This study aims to determine the effect of monochromatic light used as an artificial light source in quail cultivation management. Fifty-six DOQ quails used in this study and were divided into four treatment groups. Provision of treatment in the form of lighting using monochromatic light 12 hours per day was carried out from the age of four weeks for 3 weeks. The treatment group were P0: control quails exposured with 5 W incandescent light; P1: quails exposured with 5 W red color monochromatic light; P2: quails exposured with 5 W green color monochromatic light; P3: quails exposured with 5 W blue color monochromatic light. This study was an experimental research using a completely randomized design and Duncan further test at 95% significance level. The observed parameters, namely the average of egg weight, weight of the first egg, the number of eggs (hen day egg production), sex ripe age, feed intake, and quail body weight at first laying. These results indicated that administration of monochromatic light did not affect the sex ripe age, weight of the first egg, number of eggs (hen day egg production) and water intake, but increased the egg weight, body weight, and feed intake in quail. The conclusion of this study is the provision of monochromatic light at sex ripe age doesnâ€™t increase the number of eggs (hen day egg production). Â Keywords: monochromatic light, quail eggs (Cortunix cortunix japonica L), the production of eggs.